PENGARUH TEKNOLOGI, BRAND AWARENESS, DAN TRUST TERHADAP MINAT BELI ULANG PADA USAHA MAKANAN TRADISIONAL DI BALI - Pande Ketut Ribek; Luh Putri Mas Mirayani; Ni Kadek Andry Dwi Putri; I Kadek Adi Suswandayana; I Komang Oka Permadi (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Universitas Mahasaraswati Denpasar, Bali, Indonesia, 2024)
The research aims to determine and analyze the influence of media marketing technology and brand awareness. and trust in repurchase interest in traditional food businesses in Bali. The population in this study is traditional food customers in Tabanan Bali. Determination of the sample using the non-probability sampling method with the sampling technique carried out using purposive sampling, namely the technique of determining the sample based on certain criteria or considerations, so that the total sample used was 96 respondents. Data collection methods include observation, interviews, documentation and questionnaires. Multiple linear regression analysis technique with the SPSS program. The results of this research show that media marketing technology has a positive and significant influence on repurchase interest, brand awareness has a positive and significant influence on repurchase interest, and brand trust has a positive and significant influence on repurchase interest in traditional food in Tabanan Bali. The suggestion is that the maximum use of technology can increase repurchase interest to facilitate communication and promotion so as to increase sales value in traditional food businesses in Tabanan Bali.